Conducta obstétrica en primigesta de 39.2 semanas de embarazo con distocia de dilatación. - Gutiérrez Guerrero, Gino Geovanny (2021)
During pregnancy, mothers create an affective bond with the being they carry in their womb, hoping to have a good labor without complications, there are women who have a quiet pregnancy but sometimes during labor, difficulties appear that limit the birth These can be dilatation, birth canal and presentation dystocia, which cause conditions for the maternal-fetal pairing, forcing health professionals to make alternate decisions to correct the problem and thus guarantee a hemodynamic balance of the product. mother and fetus but above all maintain a good physical and emotional state. In this investigative work I will focus on the clinical case of a 17-year-old patient who experienced her first quiet pregnancy without alterations, but at the time of labor she had a dilatation dystocia that prevented her from exiting the fetus through the cavity. vaginal. It is important to manage an appropriate obstetric behavior in these cases to avoid maternal-fetal complications that can lead to death if it is not intervened appropriately and in a timely manner in the event of this type of dystocia.